ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHIAUDIT REPORT LAG : Studi Empiris pada Perusahaan Manufaktur yang Terdaftar diBursa Efek Indonesia Tahun 2016-2018 - Azhar Hidayatullah (2020)
This study was conducted with the aim to examine the effect of the variable Auditor Change, Company Size, and Audit Opinion on Audit Report Lag on all Manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period with a total of 185 companies. After selecting the sample criteria using the purposive sampling method, there were 72 samples of Manufacturing companies with 200 secondary data used in this study. Data analysis in this study uses multiple linear regression to test and prove the research hypothesis with a significance value of 5%. The results showed the Auditor Change and Company Size variables did not affect the Audit Lag Report as evidenced by the significance value of more than 0.05. While the Audit Opinion variable has a significant effect on Audit Report Lag on the significance value below 0.05.